The C2 Domains of Human Synaptotagmin 1 Have Distinct Mechanical Properties - Fuson, Kerry L. (The Biophysical Society, 2009)
Synaptotagmin 1 (Syt1) is the Ca(+2) receptor for fast, synchronous vesicle fusion in neurons. Because membrane fusion is an inherently mechanical, force-driven event, Syt1 must be able to adapt to the energetics of the fusion apparatus. Syt1 contains two C2 domains (C2A and C2B) that are homologous in sequence and three-dimensional in structure; yet, a number of observations have suggested that they have distinct biochemical and biological properties. In this study, we analyzed the mechanical stability of the C2A and C2B domains of human Syt1 using single-molecule atomic force microscopy. We found that stretching the C2AB domains of Syt1 resulted in two distinct unfolding force peaks. The larger force peak of ∼100 pN was identified as C2B and the second peak of ∼50 pN as C2A. Furthermore, a significant fraction of C2A domains unfolded through a low force intermediate that was not observed in C2B. We conclude that these domains have different mechanical properties. We hypothesize that a relatively small stretching force may be sufficient to deform the effector-binding regions of the C2A domain and modulate the affinity for soluble N-ethylmaleimide-sensitive factor (NSF) attachment protein receptors (SNAREs), phospholipids, and Ca(+2).